Efeitos da auto-fala no desempenho em atividades físicas: uma revisão bibliográfica - Vilela, Nathan de Paula (Universidade Federal de São Carlos, 2021)
The diferente between rule-governed and contingency-shaped behavior is largely discussed in Behavior Analysis literature. The importance of rules is remarkable in learning new skills, especially those that would take time to be learned through natural contingencies. A rule is a verbal stimulus that describes the contingency of behavior to be emitted. A type of rule used in sport psychology is self-talk, which consists of a procedure which aims to help an athlete's stimuli discrimination during sports practice or competition. This study aimed to review the experimental literature on self-talk between 2001 and 2021, in addition to verifying evidence regarding the most used types of self-talk (instructional and motivational), as well as relating the literature on self-talk to the behavior analysis literature, especially on rule-governed behavior. Altogether, twelve experimental articles which used interventions that included self talk were analyzed. In general, the results demonstrate that self-talk has a positive effect on performance in the practice of physical activities in different environments and contexts. Self talk interventions seem to be effective with people of different ages, genders and levels of competitiveness related to physical activity. Instructional self-talk proves to be effective in learning new skills and improving performance on precision tasks. Motivational self-talk proved to be effective in improving performance in strength and endurance tasks, in addition to appearing to prepare athletes for competitive situations. Still, some aspects related to the study procedure can be revisited, such as experimental control and other types of self-talk that can be included in future research. Furthermore, a low volume of articles researching self-talk in competitive contexts was observed.
Effects of self-talk on physical activity performance: a systematic review
Keywords: Auto-fala; Comportamento governado por regras; Esporte; Psicologia do esporte; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL::PROCESSOS DE APRENDIZAGEM, MEMORIA E MOTIVACAO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL